International Trade and Poverty Alleviation - Bannister, Geoffrey (IMF Working Papers; Working Paper ;, 2001)
Empirical studies suggest that trade reform has a positive effect on employment and income for the poor; however, there are winners and losers. If the transitional costs of trade liberalization fall disproportionately on the poor, trade reform can be designed to mitigate these effects. This includes making reforms as broad based as possible, sequencing and phasing them to allow for adjustment, and implementing social safety nets and other reforms that facilitate adjustment to the new trade policy. In assessing these findings, it should be borne in mind that the links between trade reform and poverty are complex, making systematic empirical investigations difficult.